Variation in gastroscopy rate in English general practice and outcome for oesophagogastric cancer: retrospective analysis of Hospital Episode Statistics. Issue 2 (20th February 2013) - Shawihdi, Mustafa; Thompson, Elizabeth; Kapoor, Neil; Powell, Geraint; Sturgess, Richard P; Stern, Nick; Roughton, Michael; Pearson, Michael G; Bodger, Keith
Abstract : Objective: To determine whether variation in gastroscopy rates in English general practice populations is associated with inequality in oesophagogastric (OG) cancer outcome. Design: Retrospective observational study of the Hospital Episode Statistics (HES) dataset for England (2006–2008) linked to death registration. Methods: were validated using independent local and national data. General practices with new cases of OG cancer were included. Practices were grouped into tertiles according to standardised elective gastroscopy rate per capita (low, medium or high). Outcome measures for cancer cases were: emergency admission during diagnostic pathway, major surgical resection and mortality at 1 year. Covariates were: age group, gender, comorbidity, general practice average deprivation and patient deprivation. Results: 22 488 incident cases of OG cancer from 6513 general practices were identified. Patients registered with the low tertile group of practices had the lowest rate of major surgery, highest rate of emergency admission and highest mortality. The inequality was widest for the most socioeconomically deprived cases. After adjustment for covariates in logistic regression, the gastroscopy rate (low, medium or high) at the patient's general practice was an independent predictor of emergency admission, major surgery and mortality. Conclusions: There is wide variation in the rate of gastroscopy among general practice populations in England. On average, OG cancer patients belonging to practices with the lowest rates of gastroscopy are at greater risk of poor outcome. These findings suggest that initiatives or current guidelines aimed at limiting the use of gastroscopy may adversely affect cancer outcomes.